Designing a Psychological Program for Self-Management for high Schools Teachers (Journal of the College of Education for Women, 2025)
The present study aims to design a psychological program for self-management among high school teachers and to prepare a suitable scale for pre- and post-test assessments suitable for the local context based on the cognitive- behavioral theory for enhancing self-management skills. The researcher adopted the descriptive- analytical- constructive method. The study consisted of two main phases: the first involved preparing the initial version of the self-management scale and the second focused on designing the psychological program of self-management.A scale was prepared to measure self-management including 34 items, with five alternatives for each item (Always, Often, Sometimes, Rarely, Never), distributed on three domains: emotions, cognitions, and behaviors. The scale was subsequently administered to a sample of high school teachers in the center of Duhok Governorate to obtain its psychometric properties, including validity and reliability, ensuring its appropriateness for practical application.Furthermore, a psychological program for self-management was constructed, comprising 16 sessions in its final form, each session was 90 minutes covering the three self-management domains. The program included an introductory session and a concluding session. Each session was structured to include an introduction, specific behavioral objectives, theoretical content, practical exercises, homework assignments, and formative assessment procedures. The program content was reviewed by experts in educational and psychological sciences, and no session was omitted; all sessions got 100% agreement rate according to their feedback.The study resulted in the preparation of a valid and reliable self- management scale suitable for application, as well as the construction of a psychological program appropriate for the teachers making it ready for implementation in the local environment. Consequently, several conclusions were drawn, and a set of conclusions, suggestions and recommendations.